Jewellery Production and Metallurgical Connectivity on the Muş Plain: A Protohistoric Bivalve Stone Mould from Saint Karapet Monastery area - Fausti, Elena; Garibian, Nazenie; Dan, Roberto (Ash-sharq: Bulletin of the Ancient Near East – Archaeological, Historical and Societal Studies, 2026)
This study presents a detailed analysis of a bivalve stone mould for jewellery production discovered near the monastery of Surb Karapet at Yukarıyongalı/Çengilli, on the Muş Plain in eastern Turkey. The findspot lies on a key east–west corridor linking the Lake Van basin to the Upper Euphrates and the Armenian Highland, an area known for its Early Bronze Age (EBA) participation in the Kura–Araxes cultural network. The finely carved steatite/serpentine mould bears multiple small matrices for geometric plaques and pendants, connected by a rational feed and vent system, with dowel holes for pin-alignment. Its technological and typological features closely match portable “trinket” moulds used across the Near East from the late 3rd to early 2nd millennium BCE, while also recalling Late Bronze Age analogues from the Levant. Comparative and contextual evidence, including EBA III metallurgical workshops at Murat Höyük (Bingöl), supports an attribution to the late EBA, though continuity of form and technique into the LBA remains plausible. The object thus offers new insight into early metallurgical connectivity and ornament production on the highland routes linking Eastern Anatolia with the Caucasus and northern Mesopotamia.